إشكالية توافق مؤهلات طالب علوم الإعلام و الاتصال مع متطلبات سوق العمل. دراسة استطلاعية لطلبة السمعي البصري بقسم علوم الإعلام والاتصال -جامعة عنابة- - عيوني, نجم الدين (جامعة الوادي - University of Eloued, 2019)
إن ظاهرة بطالة الخريجين الجدد هي إحدى المشكلات الرئيسية في الدول المتقدمة والنامية على حد سواء، بل أعقد في هذه الأخيرة لوجود إختلالات هيكلية بين التكوين وسوق العمل. وفي الجزائر أحدث الطلب الاجتماعي على التكوين والتعليم العالي زيادة متنامية في عدد المتمدرسين وفي عدد خريجي الجامعات الجدد عاما بعد عام، في غياب إستراتيجية فعالة لاستيعاب واستثمار هذه الفئة، والتي هي من حيث مبدأ التكوين الأكاديمي، مؤهلة لشغل مناصب مهنية. حيث ترتبط جودة التعليم العالي ارتباطا وثيقا بمدى فعاليته وقدرته على الاستجابة لاحتياجات المجتمع بشكل عام، وعلى هذا النحو، يتعين على الجامعة تقديم تكوين وتدريب جيد يتكيف مع انتظارات سوق العمل. وعليه تهدف هذه المداخلة إلى تسليط الضوء على مدى ارتباط المناهج البيداغوجية وأساليب التدريب في علوم الإعلام والاتصال وتحديدا تخصص السمعي البصري بالجامعة الجزائرية بمتطلبات سوق العمل. ولتحقيق ذلك تطرح هذه الدراسة مناقشة مستويين أساسيين : منهجية تصميم البرامج التعليمية في هذا التخصص وأسلوب تنظيم التعلم وممارسة التدريب من خلال دمج لمعطيات استطلاع ميداني للاندماج المهني لطلبة التخصص في طوري الليسانس والماستر بجامعة عنابة. الكلمات المفتاحية: التكوين، التدريب، المنهاج البيداغوجي، الجامعة، سوق العمل. The phenomenon of unemployment of new graduates is one of the main problems of the developed and developing countries, but even more complex in the second, because of the structural imbalances between training and the labor market. In Algeria, the social demand for higher education training has led to a steady increase in the number of students and the number of new university graduates year after year, in the absence of an effective strategy to absorb and invest in this category, which in terms of academic training is supposed to be qualified to secure professional positions. When the quality of higher education is closely linked to its effectiveness and its ability to meet the needs of society in general, as such, the university must offer good training adapted to the expectations of the labor market. The objective of this intervention is to show to what extent the pedagogical approaches and training methods of the information and communication sciences, in particular the audiovisual specialty in the Algerian university, is related to the requirements of the market work. To achieve this, the study examines two fundamental levels: the design methodology of educational programs in this specialty, the method of organization of learning and the practice of training by integrating the data of a field survey for the professional integration of undergraduate and graduate students at Annaba University.
The problem of matching the qualifications of the student in information sciences and communication with the requirements of the labor market. A Study of Audiovisual Students at the Department of Information and Communication Sciences -Annaba University
مقال
Keywords: التكوين ، التدريب ، المنهاج البيداغوجي ، الجامعة ، سوق العمل; training, internship, manual pedagogy, university, job market.